PENGARUH PENYULUHAN MENGGUNAKAN PERMAINAN ULAR TANGGA TERHADAP PENGETAHUAN KESEHATAN GIGI DAN MULUT PADA SISWA KELAS III, IV DAN V DI MI AL-ISTIQOMAH DESA GUNTUNG PAPUYU KECAMATAN GAMBUT - Najwa, Nor Raisya; Rahmawati, Hj. Ida; Sari, Emilda (Poltekkes Kemenkes Banjarmasin, 2022)
A good perception of the status of good oral and dental health will be associated with a good perception of caring for teeth, with the motivation to brush teeth in children can improve dental health so as to reduce plaque and prevent gingivitis. Meanwhile, 90% of dental caries have suffered by school children worldwide, while in Indonesia 38.5% of people in Indonesia experience dental and oral health problems. From the results of a preliminary study conducted on 10 students who were given a questionnaire about knowledge of dental and oral health at Mi Al-Istiqomah, Guntung Papuyu Village, Gambut District, it was found that 6 students were still lacking and 4 students had good knowledge. With the game of snakes and ladders, it can be equipped with interesting pictures that relate to the message conveyed and writings that are not too dense related to the content of the counseling. The purpose of this study was to determine whether there was an effect of counseling using the snake and ladder game on dental and oral health knowledge in third, fourth and fifth grade students at Mi Al-Istiqomah, Guntung Papuyu Village, Gambut District. This type of research is Quasi Experiment with One Group Pretest Posttest design. The study population was 103 students with a purposive sampling sample with a total of 43 students. Based on the results of the Paired T-Test, the value (p) is 0.000 so it is smaller than (α) = 0.05 so it can be concluded that p < , thus Ho is rejected, Ha is accepted. The conclusion is that there is an effect of counseling using the snake and ladder game on knowledge of dental and oral health. It is recommended that further researchers who want to research counseling using the snake and ladder game need to add a more creative modification of the snake and ladder board design to attract students' attention